CASE STUDY OF REPLACEMENT METHOD ON ROAD EMBANKMENT OVER A DEEP SOFT SOIL - Hanif, Basit Al; Islami, Auliya Nusyura Al (University Muhammadiyah Jakarta, 2024)
The remove-and-replace method is one method used to overcome soft soil problems. This research aims to determine the effect of replacement depth on the amount of settlement and the value of the safety factor of the embankment. The research was carried out by comparing the initial conditions with replacement depths of 0.5, 1, 1.5, and 2 meters. Analysis was carried out using the finite element method with the help of PLAXIS 2D software. From the analysis results, it was found that the largest decrease in settlement value for 2-meter replacement was 22.7% for DB-2 and 16.1% for DB-13. The 2-meter replacement also results in increased safety factor values for the DB-2 and DB-13.